Using diffusion tensor imaging to depict myocardial changes after matured pluripotent stem cell-derived cardiomyocyte transplantation - Moses P. Cook; Wahiba Dhahri; Michael A. Laflamme; Nilesh R. Ghugre; Graham A. Wright (Journal of Cardiovascular Magnetic Resonance)
Background: Novel treatment strategies are needed to improve the structure and function of the myocardium post-infarction. In vitro-matured pluripotent stem cell-derived cardiomyocytes (PSC-CMs) have been shown to be a promising regenerative strategy. We hypothesized that mature PSC-CMs will have anisotropic structure and improved cell alignment when compared to immature PSC-CMs using cardiovascular magnetic resonance (CMR) in a guinea pig model of cardiac injury. Methods: Guinea pigs (n = 16) were cryoinjured on day −10, followed by transplantation of either 108 polydimethylsiloxane (PDMS)-matured PSC-CMs (n = 6) or 108 immature tissue culture plastic (TCP)-generated PSC-CMs (n = 6) on day 0. Vehicle (sham-treated) subjects were injected with a pro-survival cocktail devoid of cells (n = 4), while healthy controls (n = 4) did not undergo cryoinjury or treatment. Animals were sacrificed on either day +14 or day +28 post-transplantation. Animals were imaged ex vivo on a 7T Bruker MRI. A 3D diffusion tensor imaging (DTI) sequence was used to quantify structure via fractional anisotropy (FA), mean diffusivity (MD), and myocyte alignment measured by the standard deviation of the transverse angle (TA). Results: MD and FA of mature PDMS grafts demonstrated anisotropy was not significantly different than the healthy control hearts (MD = 1.1 ± 0.12 × 10−3 mm2/s vs 0.93 ± 0.01 × 10−3 mm2/s, p = 0.4 and FA = 0.22 ± 0.05 vs 0.26 ± 0.001, p = 0.5). Immature TCP grafts exhibited significantly higher MD than the healthy control (1.3 ± 0.08 × 10−3 mm2/s, p < 0.05) and significantly lower FA than the control (0.12 ± 0.02, p < 0.05) but were not different from mature PDMS grafts in this small cohort. TA of healthy controls showed low variability and was not significantly different than mature PDMS grafts (p = 0.4) while immature TCP grafts were significantly different (p < 0.001). DTI parameters of mature graft tissue trended toward that of the healthy myocardium, indicating the grafted cardiomyocytes may have a similar phenotype to healthy tissue. Contrast-enhanced magnetic resonance images corresponded well to histological staining, demonstrating a non-invasive method of localizing the repopulated cardiomyocytes within the scar. Conclusions: The DTI measures within graft tissue were indicative of anisotropic structure and showed greater myocyte organization compared to the scarred territory. These findings show that MRI is a valuable tool to assess the structural impacts of regenerative therapies.